Some violations of kidney function in patients chronic obstructive pulmonary disease - Ospanova, T; Bilchenko, O; Avdeeva, E; Bolokadze, E; Veremeenko, O (Annals of Mechnikov's Institute, 2020)
The paper describes the development of pathological processes in the kidney in COPD patients. So, we have investigated indicators MAU, pulmonary function tests, lipid spectrum in patients with COPD, depending on the severity of disease. Highlighted the main pathogenetic factors of the development and progression of renal pathology in COPD.